Noneverbal Communication In Content Creator Fiersa Besari’s “Mount Agung, Atap Negeri Bali Part 3” - Rizki Dwi Nur Fajrian; Khaerudin Imawan; Novicky Alban Adiputra (CONVERSE Journal Communication Science, 2026)
The development of visual-based digital media has made nonverbal communication an important element in conveying messages, especially in video content on the YouTube platform. One content that displays the dominance of nonverbal communication is "Mount Agung, Atap Negeri Bali Part 3" by Fiersa Besari. The problems in this study are: (1) what forms of nonverbal communication are displayed, (2) how is nonverbal communication delivered, and (3) how is the meaning of the story conveyed to the audience. This study aims to: (1) determine the forms of nonverbal communication, (2) analyze the way nonverbal communication is delivered, and (3) understand the meaning of the story in the content. The research method used is a descriptive qualitative approach with content analysis techniques, through video observation, visual documentation, and in-depth interviews with five audience members. The analysis is guided by three theoretical frameworks: kinesics, theory of emotional expression, and psychoanalytic theory. The results show that nonverbal communication is displayed through three primary forms: facial expressions (such as seriousness and awe), body gestures (including slowed steps, leaning forward, and clenched fists), as well as lighting and visual composition (natural lighting, mist, shadows, and wide-angle shots). These elements play a role in conveying messages of struggle, self-reflection, and the relationship between humans and nature. Nonverbal communication is also able to build emotional experiences and strengthen the meaning of the story without relying on verbal communication. The findings demonstrate that facial expressions convey exhaustion, serenity, and amazement, while body language communicates physical effort, tenacity, and interpersonal connections. Visual lighting and composition create a contemplative atmosphere that reinforces humility and reverence toward nature. This study concludes that nonverbal communication is a key element in forming reflective narratives and emotional closeness between creators and audiences in audiovisual travel documentary content.